The first case of benign familial neonatal epilepsy diagnosed in Serbia - Nikolić, Katarina; Ješić, Maja D.; Kojić, Marko; Ješić, Miloš M. (Vojnosanitetski pregled, 2021)
Introduction. The exact prevalence of benign familial neonatal epilepsy (BFNE) is unknown due to the likelihood of overlooking the disease and not diagnosing the affected patients correctly. The rare autosomal dominant inherited disorder usually occurs within a few days after birth of an otherwise healthy newborn, and disappears after one to four months. Most patients develop no psychomotor deficiencies, nor any other forms of seizures. The disorder is most commonly linked to the KCNQ2 gene, with mutations located on the chromosome 20q13.33 which cause voltage-gated potassium channel changes. This clinically rare condition manifests itself in repeated tonic-clonic episodes of focal and generalized convulsions which are effectively treated with antiepileptic therapy. Case report. We presented a five-day old affected male infant, with genetically proven KCNQ2 gene mutation, in addition to a positive familial history of epilepsy. Seizures did not reoccur after several episodes in the fifth day of life and further psychomotor development of the child proved normal. Conclusion. Neonatal seizures have extensive differential diagnosis. However, BFNE should be suspected when the most common neonatal seizure causes have been excluded, and factors, such as the hereditary factor, in addition to the typical clinical course resembling BFNE, can be observed. Genetic identification of BFNE has resulted in easier and more specific diagnosis of this rare disorder and is therefore the gold standard in its diagnostics.